Evangélicos na mídia : a atuação dos novos agentes evangélicos midiáticos no Brasil - Costa, Poliana Marques Cordeiro (2015)
This thesis aims to understand how it has given the expansion of Evangelical culture in the media, its main features, and its consequences, searching through the identification and analysis to understand the main events involving Evangelicals in Brazil, as it relates its projection and conflicts among media, cutting for this analysis the period of 1980 through 2015, allowing thus understand the new configurations of evangelical media space today. Specifically analyzing the strategies and forms of action of New Evangelicals Media Agents that are in the evangelical field. These New Agents represent a new position in this field, taking a role that breaks with the traditional models and religious system formats. The main feature of these New Agents is their intense relationship with the media field, from which they build their position in the religious universe. Thus, the media in general, becomes one of the key features of these New Agents. It is important to analyze them through their strategies and actions, and their contributions to the conceptual formulation of what is meant by Evangelical in Brazil today, trying to understand how these New Agents make use and take possession of the Evangelical term various forms of media. Thus, understanding the use of the media as one of the main strategies mobilized by new agents to enter the religious space and compete for positions at the end, through the conceptual application presented in the dissertation was framed up as an example some new agents Evangelicals, doing- a small survey of its related them to the media center, and research on their social networks, thus seeking to show why these religious agents fall into the category of new media Agent Evangelical.